The destructive mechanism of Aβ1–42 protofibrils by norepinephrine revealed via molecular dynamics simulations. Issue 33 (10th August 2022) - Gao, Duo; Wan, Jiaqian; Zou, Yu; Gong, Yehong; Dong, Xuewei; Xu, Zhengdong; Tang, Jiaxing; Wei, Guanghong; Zhang, Qingwen
Abstract : The destructive mechanism of Aβ1–42 protofibrils by protonated and deprotonated norepinephrine revealed via molecular dynamics simulations. Abstract : Amyloid-β (Aβ) fibrillary plaques represent the main hallmarks of Alzheimer's disease (AD), in addition to tau neurofibrillary tangles. Disrupting early-formed Aβ protofibrils is considered to be one of the primary therapeutic strategies to interfere with AD. Our previous work showed that norepinephrine (NE), an important neurotransmitter in the brain, can effectively inhibit the aggregation of the Aβ1–42 peptide. However, whether and how NE molecules disassemble Aβ1–42 protofibrils remains to be elucidated. Herein we investigate the influence of NE (in protonated and deprotonated states) on the recently cryo-EM solved LS-shaped Aβ1–42 protofibrils and the underlying molecular mechanism by performing all-atom molecular dynamics simulations. Our simulations showed that protonated and deprotonated NE exhibited distinct disruptive mechanisms on Aβ1–42 protofibrils. Protonated NE could significantly disrupt the N-terminal (residues D1–H14) structure of Aβ1–42 protofibrils and destabilize the global structure of the protofibril. It preferentially bound with N-terminal residues of Aβ1–42 protofibrils and formed hydrogen bonds with E3, D7, E11, Q15, E22, and D23 residues and π–π stackings with H6, H13, and F20 residues, and thus destroyed the hydrogen bonds between H6 and E11 and increased the kink angle around Y10. Compared to protonated NE, deprotonated NE displayed a higher disruptive capability on Aβ1–42 protofibrils, and stronger hydrophobic and π–π stacking interactions with the protofibril structure. This study revealed the molecular mechanism of NE in the destruction of Aβ1–42 protofibrils, which may be helpful in the design of potent drug candidates against AD.